DEVELOPMENT OF LEGISLATIVE REGULATIONS ON CREATIVE ECONOMY EDUCATION AND INVESTMENT IN INDONESIA - Taufiq, Muchamad; Sulistina, Sulistina (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2024)
Pancasila is the foundation of Indonesian philosophy to overcome every problem in the nation's life, including economic aspect. The progress of economy research must develop properly while still paying attention to the surrounding community. It is stated in Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia that the land and water and the natural resources contained therein are controlled by the state and used for the greatest prosperity of the people. So that as a country that has the potential for great wealth both from natural resources, human resources and cultural diversity in it, then in the framework of national development, various research, and innovation are needed to optimize the potential wealth that exists. The research formulations of this study are what is the relevance of economic growth and the implementation of interdisciplinary research; and how the development of the Indonesian government's seriousness in managing interdisciplinary research. In conclusion, interdisciplinary research is a form of investment from the government for better economic growth and economic progress based on interdisciplinary research can be used as an arena for Indonesia's promotion in the academic and economic fields globally.